2019
DOI: 10.1148/radiol.2018181657
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Colorectal Hepatic Metastases Is Superior at Standard Radiation Dose CT versus Reduced Dose CT

Abstract: To evaluate colorectal cancer hepatic metastasis detection and characterization between reduced radiation dose (RD) and standard dose (SD) contrast material-enhanced CT of the abdomen and to qualitatively compare between filtered back projection (FBP) and iterative reconstruction algorithms. Materials and Methods:In this prospective study (from May 2017 through November 2017), 52 adults with biopsy-proven colorectal cancer and suspected hepatic metastases at baseline CT underwent two portal venous phase CT sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 43 publications
2
32
2
Order By: Relevance
“…Baker et al found a significantly higher image quality but degraded detection of low-contrast liver lesions at lower doses and higher strength of IR (SAFIRE, Siemens Healthineers) [ 27 ]. Jensen et al confirmed a lower detection rate of small colorectal liver metastases in low-dose protocols and different IR (ASIR and ASIR-V, GE Healthcare) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Baker et al found a significantly higher image quality but degraded detection of low-contrast liver lesions at lower doses and higher strength of IR (SAFIRE, Siemens Healthineers) [ 27 ]. Jensen et al confirmed a lower detection rate of small colorectal liver metastases in low-dose protocols and different IR (ASIR and ASIR-V, GE Healthcare) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Iterative reconstruction (IR) can provide noninferior performance for high-contrast detection tasks at lower doses; however, recent data in phantoms and abdominal CT suggest that the improvement in observer performance compared with filtered back-projection (FBP) may be limited. [8][9][10][11] Most studies examining lower-dose head CT with iterative reconstruction have relied on subjective comparisons of image quality or contrast-to-noise ratios rather than observer (ie, radiologist) performance. Practical considerations such as collecting cases with proven imaging findings, obtaining CT images at multiple doses, and correlating imaging findings between dose levels and reference standards make such research challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Mileto et al 9 recently had 16 radiologists examine a low-contrast detectability phantom and found that radiation doses resulted in similar declines in observer performance for FBP and IR and that differences among radiologists were larger than across reconstruction algorithms. Jensen et al 11 found that an approximately 50% dose reduction with one iterative reconstruction approach did not preserve observer performance for the detection of hepatic metastases. Fletcher et al 8,12 found that FBP and IR performed similarly at lower doses in detecting hepatic metastases and that IR might only be needed to maintain observer performance at a certain threshold dose.…”
Section: Discussionmentioning
confidence: 99%
“…The race to push radiation doses lower and lower in x‐ray imaging is constant . Both our inboxes and the popular radiology press continually promote the latest “studies” that estimate and extrapolate cancer risks from medical imaging, and the pursuit of the sub‐mSv CT continues despite the demonstrated risks to the patient of using radiation doses that are too low . The rejection of the LNT will end then the need to constantly tweak protocols to reduce radiation doses in pursuit of this white whale.…”
Section: For the Proposition: Aaron Kyle Jones Phdmentioning
confidence: 99%